Epidemiologia baseada em esgoto aplicada à COVID-19: análise da presença de SARS-COV-2 em esgotos urbanos de Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This study evaluated the presence of SARS-CoV-2 in raw sewage samples collected from nine Wastewater Treatment Plants (WWTPs) in the urban area of Santarém-PA, Brazil, between April and December 2023. The objective was to identify potential underreporting of COVID-19 cases and enhance the understanding of the disease's dynamics. Among the 104 samples analyzed, 59 tested positive for SARS-CoV-2, indicating community viral circulation. The results revealed an increase in viral circulation during August, September, and October 2023, coinciding with a period of low reported cases, suggesting underreporting. Wastewater-Based Epidemiology (WBE) proved to be a valuable tool for monitoring COVID-19, especially in regions with limited clinical testing. The study highlights the importance of WBE as an early warning system for outbreaks and as a complementary strategy to traditional surveillance methods.
Keywords: Águas; Vigilância; Epidemiológica; COVID-19; Residuais; CNPQ::CIÊNCIAS HUMANAS